EFL Pre-Service Teachers’ Identity and Position During Teaching Practice - Yosieka Maharani; Yuni Utami Asih; Bibit Suhatmady (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: As student teachers shift to preservice teachers during teaching practice, it is necessary to find out how teaching practice could shape their identity and position, especially in the EFL context where English is taught as a foreign language. Based on this purpose, this study seeks information on preservice teacher identity and position during teaching practice by taking discourse analysis lenses. Methodology: This study used descriptive research to describe EFL preservice teachers’ identity construction and position. Adopting Fairclough's (2013) theory relationship between language, power and social used as data analysis. An interview transcript was used to investigate the meaning behind the spoken text of two EFL preservice teachers. Findings: The finding found they shared similar identity construction across two different contexts where preservice teachers conduct their teaching practice. Starting as a student at university and transferring to school as a teacher made them construct a new identity after several times teaching students and positioned themselves in school by participating in several activities. Conclusion: It found that positioning oneself could influence the identity development of preservice teachers. However, the unexpected condition that forced them to teach online made them feel less than a teacher and try to get an identity recognized by the environment by positioning themselves in the school context. Originality: In contrast to earlier studies that investigated the anxiety of preservice EFL students, this study focused on describing how EFL preservice teachers' identity construction related to the position assigned to them in the real classroom setting.